The mathematical creative thinking ability viewed from learning interest in eleventh grade of vocational high school by using treffinger model assisted by problem card - Dwijanto, Dwijanto; Tayani, Mevi; Veronica, Rahayu Budhiati (Department of Mathematics, Universitas Negeri Semarang, 2019)
This study aimed to find out (1) whether the students’ mathematical creative thinking ability with Treffinger learning model assisted by problem cards could achieve classical completeness or not, (2) whether the average of students’ mathematical creative thinking ability with Treffinger learning model assisted by problem card can reach the Minimum Mastery Learning Criteria or KKM, (3) whether students' mathematical creative thinking ability with Treffinger's learning model assisted by problem cards was better than students’ with PBL learning model, and (4) the analysis of students' mathematical creative thinking ability in terms of students' learning interests. This research was a mixed method research. The population of this research was XI grade students of State Vocational High School 2 Rembang. The subjects of this research were selected by using random sampling techniqu. Then, XI grade of shipping engineering class B as class experiment class XI A as PBL learning class. The data collection covered method tests, questionnaires, observations, and interviews. Afterwards, the result showed that that: (1) the mathematical creative thinking ability of students in Treffinger learning assisted by problem cards achieved the classical completeness, (2) the students’ mathematical creative thinking ability in Treffinger learning assisted by problem card achieved the Minimum Mastery Learning Criteria, (3) the students’ creative thinking ability with Treffinger learning model assisted by problem card was better than students with PBL learning model, and (4) the students’ mathematical creative thinking with high interest in learning was better than students’ with the low learning interest.